PENGARUH MEDIA PEMBELAJARAN FOOD CHAIN BOARD TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPAS KELAS V UPSD SDN KAMAL 2 - Kholifatul Mukaromah; Annisa Hariyati; Silvyulla Puspita Ambarsari; Ade Cyntia Pritasari; Juhariyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study is based on poor learning outcomes in Natural and Social Sciences. This is evidenced by the fact that students in grade V have below average scores in this subject, with an average score of 61 and still below the learning objectives. The use of ineffective media to engage students is one component that influences low learning outcomes. With the help of the Food Chain Board media, this study aims to improve learning outcomes in Natural and Social Sciences on the food chain material. The data collection technique used in this study is quantitative, with a pretest, treatment, and posttest. The significant increase in students' average scores indicates the success of the learning. Student scores ranged from 61 before the exam to 83 after the exam. The results of the study indicate that the Food Chain Board learning material can improve student learning outcomes in grade V of UPTD SDN Kamal 2 in the subject of Natural and Social Sciences.